A Methodological Study of the Views of Katz and Phillips about Religious Experience - Ali Alamolhoda; Jalal Peykani; Abbas Oskouiyan; Bahman Akbari (Journal of Philosophical Investigations, 2022)
Discussing the scope of religious experience has been one of the most important topics since the eighteenth century, and from that period until now, thinkers in various fields of study such as philosophy of religion, modern theology, theology and psychology of religion and ... Has drawn various opinions in these periods about its nature and nature, the scope of its studies, its function in human life and the essence of religion or its truth or falsity. Among other things, the phenomenologists and philosophers of religion have drawn dimensions and characteristics for religion, one of which is the empirical dimension of religion. Moral, legal, and ideological precepts may contribute to the emergence of certain emotions, such as astonishment, fear, and humility, and give rise to a wonderful and exhilarating experience, such as the presence of God or the transcendent, or the glorification of mystical beings and mystical and inner experiences. Become another, to be "quite distinct" from external experiences. Because people in many different religious traditions claim to experience God, Nirvana, or Brahman, and feel that such experiences give meaning and direction to their lives. It can be acknowledged that religious experience is one of the most important issues in the psychology of religion and the philosophy of religion. In the thought of constructivists such as Pradfoot and Katz, who mostly emphasize the explanation of religious experience in its mystical dimension, they believe that the nature of religious experience is influenced by the network of beliefs and mental concepts of the subject and there are no empty experiences of beliefs and concepts. On the other hand, in Phillips's approach, religious claims, although they do not have a cognitive and narrative aspect, but to explain the statements, one can look at their application in one's social life; In other words, in order to understand religious claims, we must know the areas of life forms and pay attention to the rules of the game of religion, which is a correct belief related to a person's way of life. In the present study, while examining the methodology of these views, we try to explain and examine the views of Katz and Phillips on religious experience.